Dynasty divided: a family history of Russian and Ukrainian nationalism - Baumann, Fabian (Northern Illinois University Press, an imprint of Cornell University Press, 2023)
"This book is a study of rivaling nationalisms in nineteenth-century Kiev. It traces the story of the Shul'gin/Shul'hyn family, a political dynasty that split into Russian and Ukrainian nationalists, analyzing how they embraced national categories, cultivated their national self-images, and competed for the loyalties of Ukraine's population"--
Includes bibliographical references (pages 237- 318)and index
Keywords: Shulʹhyn family -- Political activity -- Ukraine; Shulʹhyn family -- Political activity -- Russia